Kebahagiaan pada Relawan Pelacak Kontak COVID-19 - Cahyo Harry Sancoko; Rini Sugiarti; Fendy Suhariadi (Jurnal Psikologi Teori dan Terapan, 2021)
This study aims to reveal the happiness of the COVID-19 contact tracer volunteers. A qualitative approach with a phenomenological method was employed. Five volunteers were recruited for this study. Data were collected through semistructured interviews and analyzed using an interpretative phenomenological analysis. From the results of the study, it is concluded that the happiness of being a volunteer arises from positive feelings due to perceived benefits they have given to the people in need primarily people who are recovering from COVID-19. Volunteers happiness also arises from the awareness of their positive life compared to people whose life tests are heavier than they have. The involvement and interaction of volunteers with  people who are suffering from COVID-19 makes the volunteers feel more positive and grateful for their life.Keywords: COVID-19 contact tracking, happiness, volunteers Abstrak: Penelitian ini bertujuan untuk mengetahui kebahagiaan relawan pelacak kontak COVID-19. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi. Jumlah subjek penelitian ini adalah 5 oang relawan. Pengumpulan data dilakukan melalui wawancara semiterstruktur. Data dianalisis menggunakan interpretative phenomenological analysis. Dari hasil penelitian dapat disimpulkan bahwa kebahagiaan menjadi relawan muncul karena bisa menolong dan merasakan kebahagiaan orang yang sembuh dari COVID-19. Kebahagiaan relawan juga muncul sebagai akibat melihat realita masih banyak orang lain yang ujian hidupnya lebih dari yang dialaminya. Keterlibatan dan interaksi para informan penlitian ini dengan orang yang sedang terkena penyakit COVID-19 telah membuat mereka memandang hidupnya lebih positif dan penuh kesyukuran.